2020
DOI: 10.3390/app10093288
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Methods of Compressively Sensed Image Reconstruction Based on Single-Pixel Imaging

Abstract: According to the theory of compressive sensing, a single-pixel imaging system was built in our laboratory, and imaging scenes are successfully reconstructed by single-pixel imaging, but the quality of reconstructed images in traditional methods cannot meet the demands of further engineering applications. In order to improve the imaging accuracy of our single-pixel camera, some optimization methods of key technologies in compressive sensing are proposed in this paper. First, in terms of sparse signal decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…However, the conventional reconstruction strategies are low in efficiency in terms of computation time. Wei et al [16] suggested a new mathematical model that initializes the basis differently to create binary measurement patterns that are more optimised, which results in better performance. Furthermore, post-processing of the reconstructed image has been researched in [17].…”
Section: Background a Single Pixel Imaging (Spi)mentioning
confidence: 99%
“…However, the conventional reconstruction strategies are low in efficiency in terms of computation time. Wei et al [16] suggested a new mathematical model that initializes the basis differently to create binary measurement patterns that are more optimised, which results in better performance. Furthermore, post-processing of the reconstructed image has been researched in [17].…”
Section: Background a Single Pixel Imaging (Spi)mentioning
confidence: 99%
“…However, the recently researched results show that optimized design of the measurement matrix based on minimizing the mutual coherence is not robust when the sparse representation error (SRE) is considered [18,28]. In [9,48,50], an optimized design method of measurement matrix is proposed according to the theory of minimum Frobenius norm.…”
Section: Related Workmentioning
confidence: 99%
“…The usual choices to obtain a sparse representation of natural images are the wavelet transform or the DCT [ 47 , 48 ]. The former bases are known to be mutually incoherent with structured projection matrices or even random projections for the sensing step [ 36 , 37 , 49 ]. The DCT is a transform widely employed in image compression and also in the context of CS [ 50 ].…”
Section: Cs Formulationmentioning
confidence: 99%